Small Unmanned Aircraft Systems Detect Turfgrass Drought - D. Bremer; Deon van der Merwe (Kansas Agricultural Experiment Station Research Reports, 2016)
Kansas State University is evaluating the ability of using small unmanned aircraft systems (UAS) to detect drought stress in turfgrass. Their research indicates high resolution remote sensing with small UAS can detect drought stress before it is visible to the human eye. Preliminary measurements of a golf course revealed interesting differences in fairways, tees, and greens between summer and fall seasons. Additional research will be conducted in 2016.
Keywords: unmanned aircraft systems; UAS; remote sensing; drought stress; turfgrass management; NDVI